fMLP causes degranulation followed by regranulation in rat nasal glands - Kim, Seon-Tae; Nakanaga, Takashi; Ueki, Iris; Nadel, Jay A (The Laryngoscope, 2003)
To determine the mechanism of mucus production by nasal glands. Because neutrophilic inflammation is associated with mucus hypersecretion in disease states, here we examine the role of neutrophil recruitment in mucous cell degranulation and regranulation in rat nasal glands. N-formyl-methionyl-leucyl-phenylalanine (fMLP) was aerosolized intranasally in rats (n = 5), and its effects on degranulation and regranulation of submucosal glands were evaluated by Alcian blue/periodic acid-Schiff (AB/PAS) staining and by immunolocalization of neutrophils and epidermal growth factor receptor (EGF-R). In control subjects, glands were filled with mucin. After fMLP inhalation, degranulation, 31.7 +/- 0.8% (P <.01), was maximal at 2 to 4 hours. By 24 to 48 hours after fMLP inhalation, degranulation had decreased to 10.3 +/- 0.6% (P <.05), indicating that regranulation of mucous glycoconjugates was occurring. After fMLP inhalation, neutrophils around submucosal glands increased within 0.5 hours from 1.4 +/- 0.1 to 9.5 +/- 0.3 per 0.0032 mm2 (P <.05). In control subjects, EGF-R protein was expressed near acinar ducts, 16.4 +/- 0.7% of gland area, and increased to 30.9 +/- 0.9% (P <.05) 24 to 48 hours after fMLP inhalation. Nasal pretreatment with a selective EGF-R tyrosine kinase inhibitor (BIBX1522, 15 mg/kg bid) prevented regranulation at 24 hours after fMLP inhalation (degranulation 27.8 +/- 0.3%, P <.05, compared to 24 hours after fMLP alone), indicating that inhibition of EGF-R activation had prevented regranulation after fMLP inhalation. Degranulation of rat nasal glands by fMLP is followed by regranulation; regranulation depends on a neutrophil-associated EGF-R cascade.